Multifunctional composite phase change material as well as preparation method and application thereof
By using the Pickering emulsion template method and resin and polypyrrole encapsulation technology, a highly stable and leak-free phase change energy storage microcapsule was prepared. Combined with polypyrrole-modified bacterial cellulose and polymer elastomer, a multifunctional composite phase change material was formed, which solved the problems of poor stability and application limitations of microcapsules in the existing technology and achieved excellent photothermal conversion and electrical conductivity.
Patent Information
- Application Number
- CN202411401364.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
Smart Images

Figure HDA0005075363470000011 
Figure HDA0005075363470000012 
Figure HDA0005075363470000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of phase change materials, and in particular to a multifunctional composite phase change material and a preparation method and application thereof. Background Art
[0002] Phase change materials refer to materials that undergo phase change within a certain temperature range and can absorb or release a large amount of heat energy. They have the advantages of high energy storage density and stable chemical properties and are widely used in the field of thermal energy management. Among them, organic phase change materials have the characteristics of high heat storage density, non-toxicity and low cost, and have good application prospects. However, the leakage problem of phase change materials limits their practical application.
[0003] Microencapsulation technology is a method of encapsulating phase change materials inside a shell. It is expected to solve the problem of core material leakage by isolating the core material from the external environment. However, existing phase change material microcapsules often have defects such as poor stability, complex preparation process, and low environmental protection. Microencapsulation technology based on emulsion templates, especially microcapsule materials prepared with Pickering emulsion as a template, has the characteristics of good stability, simple preparation process, and good biocompatibility. However, the Pickering emulsion template method only solves the problem in principle, and the actual process conditions need to be further explored.
[0004] The existing phase change microcapsule materials prepared by Pickering emulsion template method are basically in powder form, which is difficult to use directly and needs to be combined with other materials to meet the actual application needs. Therefore, it is of great significance to develop a phase change energy storage material with good stability, good biocompatibility, no core material leakage, simple preparation process, and can be used directly. Summary of the invention
[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a phase-change energy storage microcapsule; the second purpose of the present invention is to provide a method for preparing such a phase-change energy storage microcapsule; the third purpose of the present invention is to provide a multifunctional composite phase change material; the fourth purpose of the present invention is to provide the application of the multifunctional composite phase change material.
[0006] The basic principle of the present invention is described as follows:
[0007] The phase-change energy storage microcapsule provided by the present invention uses Pickering emulsion as a template, which can improve the stability of the microcapsule material, and then double-coats the phase-change material with resin and polypyrrole, which can not only solve the leakage problem of the phase-change material, but also improve the light-heat conversion ability and electrical conductivity of the material.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] The first aspect of the present invention provides a phase-change energy storage microcapsule, characterized in that it comprises the following preparation raw materials: a core material, a Pickering emulsion template and a wall material;
[0010] The wall material includes resin and polypyrrole.
[0011] Preferably, the core material includes at least one of alkanes, fatty acids, and high molecular weight homopolymers; further preferably, the alkanes include at least one of hexadecane, octadecane, and docosane; the fatty acids include at least one of stearic acid and palmitic acid; and the high molecular weight homopolymer includes polyethylene glycol.
[0012] Preferably, the Pickering emulsion template is an oil-in-water emulsion (O / W type).
[0013] Specifically, the use of O / W emulsion helps to evenly disperse the droplets of the oily organic phase change material, which is beneficial to improving the stability of the emulsion and facilitating the subsequent preparation of microcapsules.
[0014] Preferably, the water-to-oil ratio of the Pickering emulsion is (0.1-9):1; further preferably, the water-to-oil ratio of the Pickering emulsion is (2-3):1.
[0015] Preferably, the resin includes at least one of melamine resin, urea-formaldehyde resin and phenol-formaldehyde resin; more preferably, the resin is melamine resin (MF).
[0016] Preferably, the stabilizing particles of the Pickering emulsion template include at least one of cellulose nanocrystals, silicon dioxide, calcium carbonate, chitosan, and starch; further preferably, the stabilizing particles of the Pickering emulsion template are cellulose nanocrystals (CNC).
[0017] Specifically, cellulose nanocrystals (CNCs) have both crystalline-phobic surfaces and crystalline-philic surfaces, and can be used as a Pickering emulsion stabilizer for emulsification. Cellulose nanocrystals also have the characteristics of good biocompatibility and environmental friendliness.
[0018] Preferably, the phase-change energy storage microcapsule comprises the following preparation raw materials: core material, stabilizing particles, resin monomer, pyrrole monomer, electrostatic shielding agent, water, oxidant, and aldehyde solution.
[0019] Preferably, the electrostatic shielding agent includes a water-soluble alkali metal halogen salt; further preferably, the electrostatic shielding agent includes at least one of sodium chloride, potassium chloride, calcium chloride, and magnesium chloride; and even more preferably, the electrostatic shielding agent is sodium chloride.
[0020] Specifically, the electrostatic shielding agent can play a role in shielding ionic strength.
[0021] Preferably, the oxidant comprises FeCl3 、FeCl 3 6H 2 O、(NH 4 ) 2 S 2 O 8 , H 2 O 2 At least one of; Further preferably, the oxidant is FeCl 3 6H 2 O.FeCl 3 6H 2 O has high solubility and does not interact with other raw materials.
[0022] Preferably, the FeCl 3 6H 2 O is dissolved in the solvent to form an iron salt solution, which is then added to the reaction system as an oxidant.
[0023] Preferably, the FeCl 3 6H 2 The solvent of O is hydrochloric acid; the concentration of the hydrochloric acid is 0.5-1.5 mol / L.
[0024] Preferably, the FeCl 3 6H 2 O and the mass ratio of the solvent is 1: (100-800); further preferably, the FeCl 3 6H 2 The mass ratio of O to solvent is 1:(180-750).
[0025] Specifically, an iron salt solution is used as an oxidant to promote the oxidative self-polymerization of pyrrole monomers on the surface of the resin-coated microcapsules to form a polypyrrole nanoparticle coating layer.
[0026] Preferably, the aldehyde solution comprises an aqueous formaldehyde solution.
[0027] Preferably, the mass concentration of the aldehyde solution is 35-45%; further preferably, the mass concentration of the aldehyde solution is 35-40%.
[0028] Preferably, the resin monomer includes melamine.
[0029] The second aspect of the present invention provides a method for preparing the phase change energy storage microcapsule according to the first aspect of the present invention, comprising the following steps:
[0030] S1, mixing the stabilizing particles, the electrostatic shielding agent and water, adding the core material, and obtaining a Pickering emulsion;
[0031] S2, mixing the resin monomer and the aldehyde solution to form a resin prepolymer, and then mixing it with the Pickering emulsion to obtain a microcapsule slurry;
[0032] S3, dispersing the dry powder of the microcapsule slurry in water, adding pyrrole monomer and oxidant to obtain the phase change energy storage microcapsule.
[0033] Preferably, in step S1, the mass ratio of the stabilizing particles, the electrostatic shielding agent, water and the core material is 1:(0.7-1.5):(180-220):(75-95); further preferably, the mass ratio of the stabilizing particles, the electrostatic shielding agent, water and the core material is 1:(0.8-1.2):(190-200):(80-90).
[0034] Preferably, in step S1, the specific operation of preparing the Pickering emulsion is: firstly mixing the stable particles with water, ultrasonicating, adding an electrostatic shielding agent to obtain a stable particle dispersion; then adding the core material, reacting, and obtaining the Pickering emulsion.
[0035] Preferably, in step S1, the aqueous phase of the Pickering emulsion is an aqueous dispersion of stable particles; the dispersed phase is oily organic phase change material (core material) droplets; and the continuous phase is an aqueous dispersion of Pickering emulsion-stabilized particles.
[0036] Preferably, the ultrasound is performed in a cell disruptor; the ultrasound duration is 10-15 min.
[0037] Preferably, the reaction temperature is 40-60°C; further preferably, the reaction temperature is 45-55°C.
[0038] Preferably, the heating method of the reaction is preferably water bath heating.
[0039] Preferably, in step S2, the raw materials for preparing the resin prepolymer include: resin monomer, aldehyde solution and water.
[0040] Preferably, the mass ratio of the resin monomer, the aldehyde solution and water is 1:(1-3):(3-5); further preferably, the mass ratio of the resin monomer, the aldehyde solution and water is 1:(1-2.5):(3-4).
[0041] Preferably, the resin prepolymer is prepared by a method comprising the following steps:
[0042] The resin monomer is mixed with the aldehyde solution, water is added, the pH value is adjusted to 8-9, and the mixture is stirred and reacted at 65-75° C. for 25-35 minutes to obtain the resin prepolymer.
[0043] Preferably, in step S2, the mass ratio of the resin monomer to the Pickering emulsion-stabilized particles is (7-11):1; further preferably, the mass ratio of the resin monomer to the Pickering emulsion-stabilized particles is (8-10):1.
[0044] Preferably, in step S2, the specific operation of preparing the microcapsule slurry is: adding the resin prepolymer dropwise into the Pickering emulsion, adjusting the pH value to 3-4, and reacting to obtain the microcapsule slurry.
[0045] Preferably, the reaction time is 2-5 h; further preferably, the reaction time is 2-4 h.
[0046] Preferably, after the reaction is completed, the method further comprises the steps of filtering, drying and washing the microcapsule slurry.
[0047] Preferably, in step S3, the mass ratio of the microcapsule slurry dry powder, water, pyrrole monomer and oxidant is (20-100):(300-1500):1:(1-3); further preferably, the mass ratio of the microcapsule slurry dry powder, water, pyrrole monomer and oxidant is (24-100):(350-1500):1:(1-2).
[0048] Preferably, in step S3, the specific operation of preparing the phase change energy storage microcapsules is: firstly dispersing the dry powder of the microcapsule slurry in water to obtain a dispersion, and dispersing the pyrrole monomer in an alcohol solvent to obtain a pyrrole solution; mixing the pyrrole solution with the dispersion, stirring and reacting at low temperature to obtain a microcapsule suspension, and then adding an oxidant to the microcapsule suspension, reacting in an ice bath, and freeze-drying to obtain the phase change energy storage microcapsules.
[0049] Preferably, the solid-liquid ratio of the pyrrole monomer to the alcohol solvent is (0.03-0.2) g:1 mL; further preferably, the solid-liquid ratio of the pyrrole monomer to the alcohol solvent is (0.03-0.12) g:1 mL.
[0050] Preferably, the temperature of the low-temperature stirring reaction is 2-6°C; further preferably, the temperature of the low-temperature stirring reaction is 3-5°C.
[0051] Preferably, the low-temperature stirring reaction time is 0.5-2 h; further preferably, the low-temperature stirring reaction time is 0.5-1.5 h.
[0052] Preferably, the ice bath reaction time is 2-5 h; more preferably, the ice bath reaction temperature is 2-4 h.
[0053] Specifically, the ice bath reaction can control the reaction rate and prevent the violent polymerization of pyrrole, which would affect the material properties.
[0054] Preferably, the freeze-drying time is 40-50 h; further preferably, the freeze-drying time is 45-50 h.
[0055] The third aspect of the present invention provides a multifunctional composite phase change material, comprising the phase change energy storage microcapsule described in the first aspect of the present invention, as well as a reinforcing material and a polymer elastomer.
[0056] Preferably, the reinforcing material comprises polypyrrole-modified bacterial cellulose.
[0057] Preferably, the polypyrrole-modified bacterial cellulose is prepared by oxidative polymerization of bacterial cellulose (BC) and pyrrole monomer (Py).
[0058] Specifically, bacterial cellulose molecules have abundant hydroxyl and carboxyl groups on their surfaces, which can easily combine with polypyrrole formed by oxidative polymerization of pyrrole monomers. Bacterial cellulose has a unique three-dimensional network structure and can be modified by polypyrrole to construct thermal and electrical conductive pathways.
[0059] Preferably, the mass ratio of the bacterial cellulose to the pyrrole monomer is 1:(3-6); further preferably, the mass ratio of the bacterial cellulose to the pyrrole monomer is 1:(4-5).
[0060] Preferably, the mass ratio of the phase change energy storage microcapsules, the reinforcing material, and the polymer elastomer is (1-4):1:(1-6); further preferably, the mass ratio of the phase change energy storage microcapsules, the reinforcing material, and the polymer elastomer is (1-3):1:(1.3-6).
[0061] Preferably, the method for preparing the polypyrrole-modified bacterial cellulose specifically comprises the following steps:
[0062] The pyrrole monomer is dispersed in an alcohol solvent and added dropwise to the bacterial cellulose dispersion, and hydrochloric acid is added dropwise to obtain a bacterial cellulose-pyrrole mixed solution (BC-Py mixed solution); FeCl 3 6H 2 O is dissolved in water and added dropwise to the BC-Py mixed solution, and reacted in an ice bath to obtain the polypyrrole-modified bacterial cellulose (BC / PPy).
[0063] Preferably, the solid-liquid ratio of the pyrrole monomer to the alcohol solvent is 1 g:(1-3) mL; further preferably, the solid-liquid ratio of the pyrrole monomer to the alcohol solvent is 1 g:(1-2) mL.
[0064] Preferably, the solid content of the bacterial cellulose dispersion is 0.5-1.5 wt %; further preferably, the solid content of the bacterial cellulose dispersion is 0.8-1.2 wt %.
[0065] Preferably, the concentration of the hydrochloric acid is 1-3 mol / L; further preferably, the concentration of the hydrochloric acid is 1-2 mol / L.
[0066] Preferably, the volume of the hydrochloric acid is 8-12 mL; further preferably, the volume of the hydrochloric acid is 9-11 mL.
[0067] Preferably, the FeCl 3 6H 2 O and water mass ratio is 1: (2-4); further preferably, the FeCl 3 6H 2 The mass ratio of O to water is 1:(2-3).
[0068] Preferably, the ice bath reaction time is 1-3 h; further preferably, the ice bath reaction temperature is 1-2 h.
[0069] Preferably, the freeze-drying time is 40-50 h; further preferably, the freeze-drying time is 45-50 h.
[0070] Preferably, the polymer elastomer includes thermoplastic polyurethane (TPU).
[0071] Specifically, thermoplastic polyurethane has good flexibility and easy processability and is an ideal elastic substrate.
[0072] Preferably, the multifunctional composite phase change material is prepared by a method comprising the following steps:
[0073] The phase-change energy storage microcapsules, reinforcing materials and polymer elastomers are mixed and solution-casted to obtain the multifunctional composite phase-change material.
[0074] Preferably, the solvent for solution casting comprises N,N-dimethylformamide (DMF).
[0075] Specifically, the solution casting method can improve the uniformity and stability of multifunctional composite phase change materials.
[0076] Preferably, the mass ratio of the reinforcing material to the solvent is 1:(20-40); further preferably, the mass ratio of the reinforcing material to the solvent is 1:(30-35).
[0077] Preferably, the method for preparing the multifunctional composite phase change material specifically comprises the following steps:
[0078] The reinforcing material is dispersed in a solvent, ultrasonicated, phase-change energy storage microcapsules are added, stirred, a polymer elastomer is added, stirred for reaction, placed in a mold, vacuum degassed, and baked to obtain the multifunctional composite phase-change material.
[0079] Preferably, the ultrasonic time is 5-15 min; more preferably, the ultrasonic time is 8-12 min.
[0080] Preferably, the stirring time is 5-15 min; more preferably, the stirring time is 8-12 min.
[0081] Preferably, the stirring reaction time is 10-15 h; further preferably, the stirring reaction time is 10-12 h.
[0082] Preferably, the mold is a polytetrafluoroethylene mold.
[0083] Preferably, the vacuum degassing time is 5-15 min; further preferably, the vacuum degassing time is 8-12 min. Preferably, the baking time is 20-30 h; further preferably, the baking time is 20-25 h.
[0084] Preferably, the baking temperature is 60-80°C; more preferably, the baking temperature is 65-75°C.
[0085] The fourth aspect of the present invention provides the application of the multifunctional composite phase change material described in the third aspect of the present invention in the fields of smart wearables, solar energy conversion, and near-infrared photothermal therapy for the human body.
[0086] Compared with the prior art, the present invention has the following beneficial effects:
[0087] 1) The phase change energy storage microcapsules provided by the present invention have uniform size, regular shape, good stability, good coating effect, and the surface is doubly coated with resin and polypyrrole nanoparticles. There is no leakage of phase change material. After 100 heating and cooling cycles, the enthalpy retention rate of the microcapsules is as high as 98.9%, and the thermal cycle stability is good.
[0088] 2) The preparation method of the phase change energy storage microcapsules provided by the present invention has simple steps and mild process conditions. The addition of an electrostatic shielding agent can play a role in shielding ionic strength. The addition of an oxidant can promote the oxidative self-polymerization of pyrrole monomers on the surface of the resin-coated microcapsules to form a polypyrrole nanoparticle coating layer.
[0089] 3) The multifunctional composite phase change material provided by the present invention has a uniform structure and a regular shape. It can still retain 93% of the enthalpy value after 100 hot and cold cycles, and has good thermal cycle stability. The surface temperature under near-infrared laser irradiation is proportional to the light power, and the photothermal conversion effect is good. Under different external voltages, the surface temperature is proportional to the square of the applied voltage, which conforms to the Joule's heat law and has good Joule's heat capacity.
[0090] 4) The multifunctional composite phase change material provided by the present invention has excellent photothermal conversion ability and electrical conductivity, which can meet the application requirements in the fields of smart wearables, solar energy conversion and human near-infrared photothermal therapy, and the multifunctional composite phase change material is not in powder form and can be used directly. BRIEF DESCRIPTION OF THE DRAWINGS
[0091] Figure 1 This is a physical picture of the phase change energy storage microcapsule in Example 1;
[0092] Figure 2 is a scanning electron microscope image of the phase change energy storage microcapsule in Example 1;
[0093] Figure 3 This is a physical picture of the multifunctional composite phase change material in Example 1;
[0094] Figure 4 This is a scanning electron microscope image of the multifunctional composite phase change material in Example 1;
[0095] Figure 5 It is the DSC cycle curve diagram of the phase change energy storage microcapsule in Example 1;
[0096] Figure 6 The DSC cycle curve of the multifunctional composite phase change material in Example 1;
[0097] Figure 7 Schematic diagram of the conductive properties of the multifunctional composite phase change material in Example 1;
[0098] Figure 8 This is a test result diagram of the light-to-heat conversion performance of the multifunctional composite phase change material in Example 1;
[0099] Fig. 9 This is a graph showing the Joule thermal performance test results of the multifunctional composite phase change material in Example 1. DETAILED DESCRIPTION
[0100] The present invention is further described in detail below by specific examples. The raw materials, reagents or devices used in the examples can be obtained from conventional commercial sources or by prior art methods unless otherwise specified. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0101] Example 1
[0102] This embodiment provides a phase-change energy storage microcapsule, and a multifunctional composite phase-change material prepared using the phase-change energy storage microcapsule as a raw material:
[0103] (1) Phase change energy storage microcapsules are prepared by the following steps:
[0104] S11, adding 0.105 g of CNC to 20.79 g of water, using a cell disruptor to sonicate for 10 min, adding 0.105 g of sodium chloride thereto, shaking to fully dissolve it to obtain a CNC dispersion to form an aqueous phase; then adding 9 g of docosane to the aqueous phase, and preparing a Pickering emulsion (CNC-stabilized Pickering emulsion) by ultrasonic emulsification in a hot water bath at 50° C.;
[0105] S21, weighing 0.945 g of melamine and 1.8225 g of 37 wt % formaldehyde aqueous solution, adding 3.5 mL of deionized water and adjusting the pH to 8-9, stirring and reacting at 70° C. for 30 min to obtain MF prepolymer;
[0106] S22, adding the MF prepolymer dropwise into the Pickering emulsion template using a rubber-tipped dropper, adjusting the pH to 3-4 using 1 mol / L HCl, reacting for 3 h, filtering, washing, and drying to obtain a microcapsule slurry;
[0107] S31, 2.88g of the microcapsule slurry dry powder was dispersed in 44.55g of deionized water to form a dispersion, 0.12g of pyrrole monomer was added to 1mL of anhydrous ethanol to form a pyrrole solution; the pyrrole solution and the dispersion were mixed, and stirred at 4°C for 1h to obtain a microcapsule suspension; 0.2417g of FeCl was added to 44.55g of 1mol / L hydrochloric acid solution; 3 6H 2 O, vortex and oscillate for 1 min to obtain FeCl 3 6H 2 O solution, FeCl 3 6H 2 O solution was added dropwise into the microcapsule suspension, reacted in an ice bath for 3 h, and freeze-dried for 48 h to obtain phase change energy storage microcapsules.
[0108] (2) The multifunctional composite phase change material is prepared by the following steps:
[0109] A1. Place 40 g BC dispersion (solid content 1 wt%) in a reaction vessel, dissolve 1.8 g pyrrole monomer in 3 mL anhydrous ethanol to form a pyrrole solution, then add dropwise to the BC dispersion, then dropwise add 10 mL 1 mol / L dilute hydrochloric acid, and stir in an ice bath for 1 h to obtain a BC-Py mixed solution; add 3.6246 g FeCl 3 6H 2 O was mixed with 10 g of deionized water to form FeCl 3 6H 2O solution and added dropwise into the BC-Py mixed solution for reaction in an ice bath for 2 h. The product was filtered and washed three times with deionized water and anhydrous ethanol to make its pH neutral. It was freeze-dried for 48 h to obtain polypyrrole-modified bacterial cellulose (BC / PPy).
[0110] A2. Add 0.18g BC / PPy to 5.5g N,N-dimethylformamide, and use an ultrasonic cell crusher to sonicate for 10 minutes to evenly disperse BC / PPy in DMF; then add 0.18g phase change energy storage microcapsules, stir for 10 minutes, and then add 0.24g thermoplastic polyurethane, and stir continuously for 12 hours at room temperature; after ultrasonic treatment for 5 minutes, the obtained viscous mixture is poured into a polytetrafluoroethylene mold, vacuum degassed for 10 minutes, and vacuum-baked in an oven at 70°C for 24 hours to obtain a multifunctional composite phase change material.
[0111] Example 2
[0112] This embodiment provides a phase-change energy storage microcapsule, and a multifunctional composite phase-change material prepared using the phase-change energy storage microcapsule as a raw material:
[0113] (1) Phase change energy storage microcapsules are prepared by the following steps:
[0114] S11, adding 0.105 g of CNC to 20.79 g of water, using a cell disruptor to sonicate for 10 min, adding 0.105 g of sodium chloride thereto, shaking to fully dissolve it to obtain a CNC dispersion to form an aqueous phase; then adding 9 g of docosane to the aqueous phase, and preparing a Pickering emulsion (CNC-stabilized Pickering emulsion) by ultrasonic emulsification in a hot water bath at 50° C.;
[0115] S21, weighing 0.945 g of melamine and 1.8225 g of 37 wt % formaldehyde aqueous solution, adding 3.5 mL of deionized water and adjusting the pH to 8-9, stirring and reacting at 70° C. for 30 min to obtain MF prepolymer;
[0116] S22, adding the MF prepolymer dropwise into the Pickering emulsion using a rubber-tipped dropper, adjusting the pH to 3-4 using 1 mol / L HCl, reacting for 3 h, filtering, washing, and drying to obtain a microcapsule slurry;
[0117] S31, 2.91g of the microcapsule slurry dry powder was dispersed in 44.55g of deionized water to form a dispersion, 0.09g of pyrrole monomer was added to 1mL of anhydrous ethanol to form a pyrrole solution; the pyrrole solution and the dispersion were mixed, and stirred at 4°C for 1h to obtain a microcapsule suspension; 0.1813g of FeCl was added to 44.55g of 1mol / L hydrochloric acid solution; 3 6H 2O, vortex and oscillate for 1 min to obtain FeCl 3 6H 2 O solution, FeCl 3 6H 2 O solution was added dropwise into the microcapsule suspension, reacted in an ice bath for 3 h, and freeze-dried for 48 h to obtain phase change energy storage microcapsules.
[0118] (2) The multifunctional composite phase change material is prepared by the following steps:
[0119] A1. Place 40 g BC dispersion (solid content 1 wt%) in a reaction vessel, dissolve 1.8 g pyrrole monomer in 3 mL anhydrous ethanol to form a pyrrole solution, then add dropwise to the BC dispersion, then dropwise add 10 mL 1 mol / L dilute hydrochloric acid, and stir in an ice bath for 1 h to obtain a BC-Py mixed solution; add 3.6246 g FeCl 3 6H 2 O was mixed with 10 g of deionized water to form FeCl 3 6H 2 O solution and added dropwise into the BC-Py mixed solution for reaction in an ice bath for 2 h. The product was filtered and washed three times with deionized water and anhydrous ethanol to make its pH neutral. It was freeze-dried for 48 h to obtain polypyrrole-modified bacterial cellulose (BC / PPy).
[0120] A2. Add 0.18g BC / PPy to 5.5g N,N-dimethylformamide, and use an ultrasonic cell crusher to sonicate for 10 minutes to evenly disperse BC / PPy in DMF; then add 0.18g phase change energy storage microcapsules, stir for 10 minutes, and then add 0.24g thermoplastic polyurethane, and stir continuously for 12 hours at room temperature; after ultrasonic treatment for 5 minutes, the obtained viscous mixture is poured into a polytetrafluoroethylene mold, vacuum degassed for 10 minutes, and vacuum-baked in an oven at 70°C for 24 hours to obtain a multifunctional composite phase change material.
[0121] Example 3
[0122] This embodiment provides a phase-change energy storage microcapsule, and a multifunctional composite phase-change material prepared using the phase-change energy storage microcapsule as a raw material:
[0123] (1) Phase change energy storage microcapsules are prepared by the following steps:
[0124] S11, adding 0.105 g of CNC to 20.79 g of water, using a cell disruptor to sonicate for 10 min, adding 0.105 g of sodium chloride thereto, shaking to fully dissolve it to obtain a CNC dispersion to form an aqueous phase; then adding 9 g of docosane to the aqueous phase, and preparing a Pickering emulsion (CNC-stabilized Pickering emulsion) by ultrasonic emulsification in a hot water bath at 50° C.;
[0125] S21, weighing 0.945 g of melamine and 1.8225 g of 37 wt % formaldehyde aqueous solution, adding 3.5 mL of deionized water and adjusting the pH to 8-9, stirring and reacting at 70° C. for 30 min to obtain MF prepolymer;
[0126] S22, adding the MF prepolymer dropwise into the Pickering emulsion using a rubber-tipped dropper, adjusting the pH to 3-4 using 1 mol / L HCl, reacting for 3 h, filtering, washing, and drying to obtain a microcapsule slurry;
[0127] S31, 2.94g of the microcapsule slurry dry powder was dispersed in 44.55g of deionized water to form a dispersion, 0.06g of pyrrole monomer was added to 1mL of anhydrous ethanol to form a pyrrole solution; the pyrrole solution and the dispersion were mixed, and stirred at 4°C for 1h to obtain a microcapsule suspension; 0.1209g of FeCl was added to 44.55g of 1mol / L hydrochloric acid solution; 3 6H 2 O, vortex and oscillate for 1 min to obtain FeCl 3 6H 2 O solution, FeCl 3 6H 2 O solution was added dropwise into the microcapsule suspension, reacted in an ice bath for 3 h, and freeze-dried for 48 h to obtain phase change energy storage microcapsules.
[0128] (2) The multifunctional composite phase change material is prepared by the following steps:
[0129] A1. Place 40 g BC dispersion (solid content 1 wt%) in a reaction vessel, dissolve 1.8 g pyrrole monomer in 3 mL anhydrous ethanol to form a pyrrole solution, then add dropwise to the BC dispersion, then dropwise add 10 mL 1 mol / L dilute hydrochloric acid, and stir in an ice bath for 1 h to obtain a BC-Py mixed solution; add 3.6246 g FeCl 3 6H 2 O was mixed with 10 g of deionized water to form FeCl 3 6H 2 O solution and added dropwise into the BC-Py mixed solution for reaction in an ice bath for 2 h. The product was filtered and washed three times with deionized water and anhydrous ethanol to make its pH neutral. It was freeze-dried for 48 h to obtain polypyrrole-modified bacterial cellulose (BC / PPy).
[0130] A2. Add 0.18g BC / PPy to 5.5g N,N-dimethylformamide, and use an ultrasonic cell crusher to sonicate for 10 minutes to evenly disperse BC / PPy in DMF; then add 0.18g phase change energy storage microcapsules, stir for 10 minutes, and then add 0.24g thermoplastic polyurethane, and stir continuously for 12 hours at room temperature; after ultrasonic treatment for 5 minutes, the obtained viscous mixture is poured into a polytetrafluoroethylene mold, vacuum degassed for 10 minutes, and vacuum-baked in an oven at 70°C for 24 hours to obtain a multifunctional composite phase change material.
[0131] Example 4
[0132] This embodiment provides a phase-change energy storage microcapsule, and a multifunctional composite phase-change material prepared using the phase-change energy storage microcapsule as a raw material:
[0133] (1) Phase change energy storage microcapsules are prepared by the following steps:
[0134] S11, adding 0.105 g of CNC to 20.79 g of water, using a cell disruptor to sonicate for 10 min, adding 0.105 g of sodium chloride thereto, shaking to fully dissolve it to obtain a CNC dispersion to form an aqueous phase; then adding 9 g of docosane to the aqueous phase, and preparing a Pickering emulsion (CNC-stabilized Pickering emulsion) by ultrasonic emulsification in a hot water bath at 50° C.;
[0135] S21, weighing 0.945 g of melamine and 1.8225 g of 37 wt % formaldehyde aqueous solution, adding 3.5 mL of deionized water and adjusting the pH to 8-9, stirring and reacting at 70° C. for 30 min to obtain MF prepolymer;
[0136] S22, adding the MF prepolymer dropwise into the Pickering emulsion using a rubber-tipped dropper, adjusting the pH to 3-4 using 1 mol / L HCl, reacting for 3 h, filtering, washing, and drying to obtain a microcapsule slurry;
[0137] S31, 2.97g of the microcapsule slurry dry powder was dispersed in 44.55g of deionized water to form a dispersion, 0.03g of pyrrole monomer was added to 1mL of anhydrous ethanol to form a pyrrole solution; the pyrrole solution and the dispersion were mixed, and stirred at 4°C for 1h to obtain a microcapsule suspension; 0.0604g of FeCl was added to 44.55g of 1mol / L hydrochloric acid solution; 3 6H 2 O, vortex and oscillate for 1 min to obtain FeCl 3 6H 2 O solution, FeCl 3 6H 2O solution was added dropwise into the microcapsule suspension, reacted in an ice bath for 3 h, and freeze-dried for 48 h to obtain phase change energy storage microcapsules.
[0138] (2) The multifunctional composite phase change material is prepared by the following steps:
[0139] A1. Place 40 g BC dispersion (solid content 1 wt%) in a reaction vessel, dissolve 1.8 g pyrrole monomer in 3 mL anhydrous ethanol to form a pyrrole solution, then add dropwise to the BC dispersion, then dropwise add 10 mL 1 mol / L dilute hydrochloric acid, and stir in an ice bath for 1 h to obtain a BC-Py mixed solution; add 3.6246 g FeCl 3 6H 2 O was mixed with 10 g of deionized water to form FeCl 3 6H 2 O solution and added dropwise into the BC-Py mixed solution for reaction in an ice bath for 2 h. The product was filtered and washed three times with deionized water and anhydrous ethanol to make its pH neutral. It was freeze-dried for 48 h to obtain polypyrrole-modified bacterial cellulose (BC / PPy).
[0140] A2. Add 0.18g BC / PPy to 5.5g N,N-dimethylformamide, and use an ultrasonic cell crusher to sonicate for 10 minutes to evenly disperse BC / PPy in DMF; then add 0.18g phase change energy storage microcapsules, stir for 10 minutes, and then add 0.24g thermoplastic polyurethane, and stir continuously for 12 hours at room temperature; after ultrasonic treatment for 5 minutes, the obtained viscous mixture is poured into a polytetrafluoroethylene mold, vacuum degassed for 10 minutes, and vacuum-baked in an oven at 70°C for 24 hours to obtain a multifunctional composite phase change material.
[0141] Example 5
[0142] This embodiment provides a phase-change energy storage microcapsule, and a multifunctional composite phase-change material prepared using the phase-change energy storage microcapsule as a raw material:
[0143] (1) Phase change energy storage microcapsules are prepared by the following steps:
[0144] S11, adding 0.105 g of CNC to 20.79 g of water, using a cell disruptor to sonicate for 10 min, adding 0.105 g of sodium chloride thereto, shaking to fully dissolve it to obtain a CNC dispersion to form an aqueous phase; then adding 9 g of docosane to the aqueous phase, and preparing a Pickering emulsion (CNC-stabilized Pickering emulsion) by ultrasonic emulsification in a hot water bath at 50° C.;
[0145] S21, weighing 0.945 g of melamine and 1.8225 g of 37 wt % formaldehyde aqueous solution, adding 3.5 mL of deionized water and adjusting the pH to 8-9, stirring and reacting at 70° C. for 30 min to obtain MF prepolymer;
[0146] S22, adding the MF prepolymer dropwise into the Pickering emulsion using a rubber-tipped dropper, adjusting the pH to 3-4 using 1 mol / L HCl, reacting for 3 h, filtering, washing, and drying to obtain a microcapsule slurry;
[0147] S31, 2.88g of the microcapsule slurry dry powder was dispersed in 44.55g of deionized water to form a dispersion, 0.12g of pyrrole monomer was added to 1mL of anhydrous ethanol to form a pyrrole solution; the pyrrole solution and the dispersion were mixed, and stirred at 4°C for 1h to obtain a microcapsule suspension; 0.2417g of FeCl was added to 44.55g of 1mol / L hydrochloric acid solution; 3 6H 2 O, vortex and oscillate for 1 min to obtain FeCl 3 6H 2 O solution, FeCl 3 6H 2 O solution was added dropwise into the microcapsule suspension, reacted in an ice bath for 3 h, and freeze-dried for 48 h to obtain phase change energy storage microcapsules.
[0148] (2) The multifunctional composite phase change material is prepared by the following steps:
[0149] A1. Place 40 g BC dispersion (solid content 1 wt%) in a reaction vessel, dissolve 1.8 g pyrrole monomer in 3 mL anhydrous ethanol to form a pyrrole solution, then add dropwise to the BC dispersion, then dropwise add 10 mL 1 mol / L dilute hydrochloric acid, and stir in an ice bath for 1 h to obtain a BC-Py mixed solution; add 3.6246 g FeCl 3 6H 2 O was mixed with 10 g of deionized water to form FeCl 3 6H 2 O solution and added dropwise into the BC-Py mixed solution for reaction in an ice bath for 2 h. The product was filtered and washed three times with deionized water and anhydrous ethanol to make its pH neutral. It was freeze-dried for 48 h to obtain polypyrrole-modified bacterial cellulose (BC / PPy).
[0150] A2. Add 0.18g BC / PPy to 5.5g N,N-dimethylformamide, and use an ultrasonic cell crusher to sonicate for 10 minutes to evenly disperse BC / PPy in DMF; then add 0.12g phase change energy storage microcapsules, stir for 10 minutes, and then add 0.3g thermoplastic polyurethane, and stir continuously for 12 hours at room temperature; after ultrasonic treatment for 5 minutes, the obtained viscous mixture is poured into a polytetrafluoroethylene mold, vacuum degassed for 10 minutes, and vacuum-baked in an oven at 70°C for 24 hours to obtain a multifunctional composite phase change material.
[0151] Example 6
[0152] This embodiment provides a phase-change energy storage microcapsule, and a multifunctional composite phase-change material prepared using the phase-change energy storage microcapsule as a raw material:
[0153] (1) Phase change energy storage microcapsules are prepared by the following steps:
[0154] S11, adding 0.105 g of CNC to 20.79 g of water, using a cell disruptor to sonicate for 10 min, adding 0.105 g of sodium chloride thereto, shaking to fully dissolve it to obtain a CNC dispersion to form an aqueous phase; then adding 9 g of docosane to the aqueous phase, and preparing a Pickering emulsion (CNC-stabilized Pickering emulsion) by ultrasonic emulsification in a hot water bath at 50° C.;
[0155] S21, weighing 0.945 g of melamine and 1.8225 g of 37 wt % formaldehyde aqueous solution, adding 3.5 mL of deionized water and adjusting the pH to 8-9, stirring and reacting at 70° C. for 30 min to obtain MF prepolymer;
[0156] S22, adding the MF prepolymer dropwise into the Pickering emulsion using a rubber-tipped dropper, adjusting the pH to 3-4 using 1 mol / L HCl, reacting for 3 h, filtering, washing, and drying to obtain a microcapsule slurry;
[0157] S31, 2.88g of the microcapsule slurry dry powder was dispersed in 44.55g of deionized water to form a dispersion, 0.12g of pyrrole monomer was added to 1mL of anhydrous ethanol to form a pyrrole solution; the pyrrole solution and the dispersion were mixed, and stirred at 4°C for 1h to obtain a microcapsule suspension; 0.2417g of FeCl was added to 44.55g of 1mol / L hydrochloric acid solution; 3 6H 2 O, vortex and oscillate for 1 min to obtain FeCl 3 6H 2 O solution, FeCl 3 6H 2O solution was added dropwise into the microcapsule suspension, reacted in an ice bath for 3 h, and freeze-dried for 48 h to obtain phase change energy storage microcapsules.
[0158] (2) The multifunctional composite phase change material is prepared by the following steps:
[0159] A1. Place 40 g BC dispersion (solid content 1 wt%) in a reaction vessel, dissolve 1.8 g pyrrole monomer in 3 mL anhydrous ethanol to form a pyrrole solution, then add dropwise to the BC dispersion, then dropwise add 10 mL 1 mol / L dilute hydrochloric acid, and stir in an ice bath for 1 h to obtain a BC-Py mixed solution; add 3.6246 g FeCl 3 6H 2 O was mixed with 10 g of deionized water to form FeCl 3 6H 2 O solution and added dropwise into the BC-Py mixed solution for reaction in an ice bath for 2 h. The product was filtered and washed three times with deionized water and anhydrous ethanol to make its pH neutral. It was freeze-dried for 48 h to obtain polypyrrole-modified bacterial cellulose (BC / PPy).
[0160] A2. Add 0.18g BC / PPy to 5.5g N,N-dimethylformamide, and use an ultrasonic cell crusher to ultrasonicate for 10 minutes to evenly disperse BC / PPy in DMF; then add 0.06g phase change energy storage microcapsules, stir for 10 minutes, and then add 0.36g thermoplastic polyurethane, and stir continuously for 12 hours at room temperature; after ultrasonic treatment for 5 minutes, the obtained viscous mixture is poured into a polytetrafluoroethylene mold, vacuum degassed for 10 minutes, and vacuum-baked in an oven at 70°C for 24 hours to obtain a multifunctional composite phase change material.
[0161] Material Characterization and Performance Testing
[0162] 1. Morphology observation of phase change energy storage microcapsules and multifunctional composite phase change materials in Example 1:
[0163] The morphology of the phase-change energy storage microcapsules in Example 1 was observed with the naked eye. Figure 1 is a physical picture of the phase change energy storage microcapsule in Example 1, Figure 1 It can be seen that the phase-change energy storage microcapsules prepared in Example 1 are in a uniform powder state, and no agglomerated docosane solids appear, indicating that the phase-change energy storage microcapsules provided by the present invention have no leakage of phase-change materials.
[0164] The morphology of the phase change energy storage microcapsules in Example 1 was observed using a scanning electron microscope. Figure 2 is a scanning electron microscope image of the phase change energy storage microcapsule in Example 1, Figure 2It can be seen that the phase change energy storage microcapsules in Example 1 are spherical structures of uniform size with a particle diameter of 1-10 μm. The coverage rate of the phase change energy storage microcapsules is high, and the surface of each microcapsule is coated with polypyrrole nanoparticles, which is beneficial to improving the photothermal conversion ability and conductivity of the microcapsules.
[0165] Observe the morphology of the multifunctional composite phase change material in Example 1 with the naked eye. Figure 3 is a physical picture of the multifunctional composite phase change material in Example 1, Figure 3 It can be seen that the surface of the multifunctional composite phase change material is smooth, and there are no microcapsule powders and BC / PPy solid particles, indicating that the compatibility between the various preparation raw materials of the multifunctional composite phase change material is good and the structural uniformity of the composite material is good.
[0166] The cross-sectional morphology of the multifunctional composite phase change material in Example 1 was observed using a scanning electron microscope. Figure 4 is a scanning electron microscope image of the multifunctional composite phase change material in Example 1, Figure 4 It can be seen that the dense network structure of BC / PPy and TPU runs through the entire composite film, and the docosane phase change microcapsules are evenly distributed in the film and interconnected through the BC / PPy network, which is beneficial to further enhance the photothermal conversion and conductivity of the microcapsules.
[0167] 2. Cyclic performance test of phase change energy storage microcapsules and multifunctional composite phase change materials in Example 1:
[0168] The phase change enthalpy performance test of the phase change energy storage microcapsules and the multifunctional composite phase change material in Example 1 was carried out using differential scanning calorimetry (DSC) Q2000 (TA Company, USA). Figure 5 is the DSC cycle curve of the phase change energy storage microcapsule in Example 1, Figure 5 It can be seen that after the phase-change energy storage microcapsules in Example 1 have been subjected to 100 heating and cooling cycles, the microcapsule enthalpy retention rate is as high as 98.9%, indicating that the phase-change energy storage microcapsules provided by the present invention have extremely high thermal cycle stability.
[0169] Figure 6 is the DSC cycle curve of the multifunctional composite phase change material in Example 1, Figure 6 It can be seen that after 100 heating and cooling cycles, the enthalpy retention rate of the multifunctional composite phase change material reaches 93%, indicating that the multifunctional composite phase change material provided by the present invention has the same excellent thermal cycle stability as the phase change energy storage microcapsule.
[0170] 3. Conductive performance test of the multifunctional composite phase change material in Example 1:
[0171] Figure 7 is a schematic diagram of the conductive properties of the multifunctional composite phase change material in Example 1, Figure 7 It can be seen that the LED light bulb can be successfully lit by using the multifunctional composite phase change material in Example 1 as a part of the conductive path, which indicates that the multifunctional composite phase change material provided by the present invention has good conductivity.
[0172] 4. Test the photothermal conversion performance of the multifunctional composite phase change material in Example 1 under near-infrared lasers of different powers:
[0173] The multifunctional composite phase change material in Example 1 was tested at 0.4 W / cm 2 , 0.7W / cm 2 , 1.2W / cm 2 and 1.6W / cm 2 Photothermal conversion performance under high-power near-infrared laser, Figure 8 The photothermal conversion performance test result diagram of the multifunctional composite phase change material in Example 1 is shown in FIG. Figure 8 It can be seen that with the increase of near-infrared light intensity, the maximum stable temperature of the multifunctional composite phase change material continues to rise, 0.4W / cm 2 , 0.7W / cm 2 , 1.2W / cm 2 and 1.6W / cm 2 The highest stable temperatures under different powers are 48.1°C, 69.5°C, 92.9°C and 123.5°C respectively, and the highest stable temperature is proportional to the light intensity, indicating that the multifunctional composite phase change material provided by the present invention has good light-to-heat conversion ability.
[0174] 5. Test the Joule heating performance of the multifunctional composite phase change material in Example 1 under different applied voltages:
[0175] The surface temperature of the multifunctional composite phase change material in Example 1 under applied voltages of 5V, 6V, 7V and 8V was tested respectively. Fig. 9 The Joule thermal performance test result diagram of the multifunctional composite phase change material in Example 1 is shown in FIG. Fig. 9 It can be seen that under the applied voltages of 5V, 6V, 7V and 8V, the surface temperatures of the multifunctional composite phase change material are 48.1°C, 58.2°C, 70.4°C and 85.2°C respectively, and the surface temperature is proportional to the square of the applied voltage, which conforms to the Joule's heat law, indicating that the multifunctional composite phase change material provided by the present invention has good Joule heat performance.
[0176] The phase change energy storage microcapsules provided by the present invention have uniform particle size, good coating effect, no leakage of phase change materials, and good thermal cycle stability; the multifunctional composite phase change material prepared with phase change energy storage microcapsules as raw materials is non-powdered and can be used directly, and the multifunctional composite phase change material has excellent light-heat conversion capacity, Joule heat capacity and electrical conductivity, and can meet the application requirements of multi-functions and multiple scenarios.
Claims
1. A phase change energy storage microcapsule, characterized in that: The preparation comprises the following raw materials: core material, Pickering emulsion template and wall material; The wall material includes resin and polypyrrole.
2. The phase change energy storage microcapsule according to claim 1, characterized in that: The Pickering emulsion is an oil-in-water emulsion; The water-oil ratio is (0.1-9):1; And / or, the stabilizing particles of the Pickering emulsion template include at least one of cellulose nanocrystals, silicon dioxide, calcium carbonate, chitosan, and starch.
3. The phase change energy storage microcapsule according to claim 2, characterized in that: The phase-change energy storage microcapsule comprises the following preparation raw materials: core material, stabilizing particles, resin monomer, pyrrole monomer, electrostatic shielding agent, water, oxidant and aldehyde solution.
4. The method for preparing the phase-change energy storage microcapsule according to claim 3, characterized in that: The following steps are involved: S1, mixing the stabilizing particles, the electrostatic shielding agent and water, adding the core material, and obtaining a Pickering emulsion; S2, mixing the resin monomer and the aldehyde solution to form a resin prepolymer, and then mixing it with the Pickering emulsion to obtain a microcapsule slurry; S3, dispersing the dry powder of the microcapsule slurry in water, adding pyrrole monomer and oxidant to obtain the phase change energy storage microcapsule.
5. The preparation method according to claim 4, characterized in that: In the step S1, the mass ratio of the stabilizing particles, the electrostatic shielding agent, the water and the core material is 1:(0.7-1.5):(180-220):(75-95); And / or, in step S2, the mass ratio of the resin monomer to the Pickering emulsion stabilized particles is (7-11):1; And / or, in step S3, the mass ratio of the microcapsule slurry dry powder, water, pyrrole monomer and oxidant is (20-100):(300-1500):1:(1-3).
6. A multifunctional composite phase change material, characterized in that: The preparation method comprises the following raw materials: the phase-change energy storage microcapsule according to any one of claims 1 to 3, and a reinforcing material and a polymer elastomer.
7. The multifunctional composite phase change material according to claim 6, characterized in that: The reinforcing material includes polypyrrole-modified bacterial cellulose; And / or, the polypyrrole-modified bacterial cellulose is prepared by oxidative polymerization of bacterial cellulose and pyrrole monomers; And / or, the mass ratio of the bacterial cellulose to the pyrrole monomer is 1:(3-6).
8. The multifunctional composite phase change material according to claim 6, characterized in that: The mass ratio of the phase change energy storage microcapsule, the reinforcing material and the polymer elastomer is (1-4):1:(1-6).
9. The multifunctional composite phase change material according to claim 8, characterized in that: The multifunctional composite phase change material is prepared by a method comprising the following steps: The phase-change energy storage microcapsules, reinforcing materials and polymer elastomers are mixed and solution-casted to obtain the multifunctional composite phase-change material.
10. Application of the multifunctional composite phase change material according to any one of claims 6 to 9 in the fields of smart wearables, solar energy conversion, and near-infrared photothermal therapy for human body.
Citation Information
Cited By
Photo-thermal phase change energy storage composite fabric as well as preparation method and application thereof
CN119932931A
Flexible composite phase change material based on water-in-oil Pickering emulsion method in-situ packaging and preparation method thereof
CN122563558A